A sufficient condition for the real Jacobian conjecture in R2. (August 2021) - Llibre, Jaume; Valls, Claudia
Abstract: Let F = ( f, g ) : R 2 → R 2 be a polynomial map such that det D F ( x, y ) is different from zero for all ( x, y ) ∈ R 2 . We provide some new sufficient conditions for the injectivity of F . The proofs are based on the qualitative theory of differential equations.